The theory and measurement of elasticcity of substitution in international trade - Stern, Robert M (Blackwell Publishing Ltd, 2023)
A number of empirical studies attempting to measure the elasticity of substitution in the international trade of competing countries have appeared in the postwar period2. These studies have had in mind such important problems as the effects of devaluation, and the deter mination of a country’s price competitiveness and hence its share of world and regional export markets.